Implementasi Konsep Sistem Mobil pada Perancangan Interior Bengkel Mobil “Kusuma Motor” di Surabaya - Flora Indah Kusuma; Ronald Hasudungan Irianto Sitinjak; Linggajaya Suryanata (Intra, 2018)
The number of cars is currently growing rapidly in Indonesia, especially in big cities like Surabaya. Along with the increasing number of cars, the number of car repair services are also increasing. Considering that car owners want their cars to always look excellent. One of the supporting factors to add more value to the car repair service is by providing nice interior design that will comfort the visitors. From the observation, there is still no public car repair service with the same quality and facilities as authorized services. The Interior Design of